Global Solutions for an -Component System of Activator-Inhibitor Type - S. Abdelmalek; A. Gouadria; A. Youkana (Abstract and Applied Analysis)
This paper deals with a reaction-diffusion system with fractional reactions modeling -substances into interaction following activator-inhibitor's scheme. The existence of global solutions is obtained via a judicious Lyapunov functional that generalizes the one introduced by Masuda and Takahashi.